Prosedur Pencatatan Perkawinan dan Perceraian di Negara Indonesia dan Malaysia Perspektif Hukum Islam - Fahmi Basyar (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2017)
One phenomenon that emerged in the Islamic world in the 20th century is the family law renewal efforts undertaken by countries with Muslim majority. This was done in response to the dynamic development of society life. There are at least three points that is the objective of family law renewal in the Islamic world, as a law unification effort, raising the status of female, and responding to developments and demands to provide solutions to existing problems. A review of Act Number 1 in 1974 "named this law as a form of unification that is unique with respect fully the variation based on religion and belief to God, besides that unification aims to complement what is not regulated by religion, because in that matter, the state has the right to set it in accordance with the developments and the demands. From the aspect of the history of the Islamic family law renewal in South East Asia spearheaded by Malaysia. It is the first country that has been undertaking the renewal effort, with the birth of Mohammad Marriage Ordinance Number 5 in 1880 in the countries of the straits.